Overestimation of hours dedicated to family caregiving of persons with heart failure - Timonet Andreu, Eva María; Canca-Sánchez, José Carlos; Sepulveda-Sanchez, juana; ortiz-tome, celia; Rivas-Ruiz, Francisco; Toribio, Juan Carlos; Mora-Banderas, Ana María; Morales-Asencio, José Miguel (Wiley, 2018)
Abstract Aims: The aim of this study is to profile the family caregivers of people living with heart failure, to determine the perceived and real time devoted to daily care and to identify the factors associated with caregivers' overestimation of time dedicated to care. Background: The time spent by family caregivers on daily care is related to overload, but there are differences between real and perceived time spent. The reason for this difference is unknown, as is its impact on the caregiver. Design: Multicentre, cross-sectional study. Methods: This study forms part of a longitudinal, multicentre, ambispective cohort investigation. The study population was composed of 478 patient-family caregiver dyads and the data were collected over 2 years from 2014 - 2016. Results: The mean time perceived to be spent on daily care was 8.79 hr versus a real value of 4.41 hr. These values were positively correlated. A significant correlation was also found between the overestimation of hours spent and the age of the caregiver, the duration of the caregiving relationship and the number of people providing support and with the patient's level of dependence and self-care. Conclusion: The overestimation of time dedicated to care seems to be related to patients' and caregivers' characteristics, such as functional status, caregiver burden, age and cohabitation. These patterns should be considered by nurses when carrying out assessment and care planning with these patients and their caregivers. Keywords: caregivers; chronic disease; heart failure; nursing; questionnaire.
Keywords: Vida familiar; Insuficiencia cardíaca; Caregivers